2001
DOI: 10.1038/nn787
|View full text |Cite
|
Sign up to set email alerts
|

Two cDNAs coding for histamine-gated ion channels in D. melanogaster

Abstract: Histamine, a neurotransmitter and neuroregulatory compound in diverse species, serves as the neurotransmitter of photoreceptors in insects and other arthropods by directly activating a chloride channel. By systematic expression screening of novel putative ligand-gated anion channels, we identified two cDNAs (DM-HisCl-alpha 1 and-alpha 2) coding for putative histamine-gated chloride channels by functional expression in Xenopus laevis oocytes. DM-HisCl-alpha 1 mRNA localizes in the lamina region of the Drosophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
130
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(140 citation statements)
references
References 15 publications
9
130
1
Order By: Relevance
“…Histamine receptor antagonists cause the hdc null mutantlike abnormal temperature preferences It was reported that compounds able to competitively inhibit histamine receptors in humans, such as cimetidine and hydroxyzine, can effectively inhibit fruit fly histamine receptors in vivo and ex vivo (Gisselmann et al, 2002;Shaw et al, 2000). Therefore, we tested whether wild-type flies treated with these inhibitors show altered temperature preferences like the hdc null mutant or receptor DKO.…”
Section: Ep Lines Linked To the Genes Of The Histaminergic System Shomentioning
confidence: 99%
See 1 more Smart Citation
“…Histamine receptor antagonists cause the hdc null mutantlike abnormal temperature preferences It was reported that compounds able to competitively inhibit histamine receptors in humans, such as cimetidine and hydroxyzine, can effectively inhibit fruit fly histamine receptors in vivo and ex vivo (Gisselmann et al, 2002;Shaw et al, 2000). Therefore, we tested whether wild-type flies treated with these inhibitors show altered temperature preferences like the hdc null mutant or receptor DKO.…”
Section: Ep Lines Linked To the Genes Of The Histaminergic System Shomentioning
confidence: 99%
“…Immunohistochemical studies indicated the presence of histamine in a variety of neuron types in the brain and optic lobes, as well as in the ganglia of the ventral nerve cord of several insect species (for review, see Nässel, 1999). In arthropods, it was reported that histamine increases chloride conductance (Claiborne and Selverston, 1984;Hardie, 1989;McClintock and Ache, 1989;Gisselmann et al, 2002) and that its receptors are members of the ligand-gated chloride channel family.…”
Section: Introductionmentioning
confidence: 99%
“…Third, at glycinergic synapses onto intact zebrafish hindbrain (Mauthner) neurons, zinc chelators decreased the amplitude, duration, and frequency of glycinergic inhibitory postsynaptic currents, whereas zinc application had the opposite effect (9). The GlyR is a member of the ligand-gated ion channel (LGIC) receptor family, which includes the nicotinic acetylcholine receptor cation channel (nAChR), the ␥-aminobutyric acid type-A and type-C receptor chloride channels (GABA A R and GABA C R), the serotonin receptor cation channel (5HT 3 R), and a recently identified zinc-gated cation channel (10) as well as invertebrate glutamate and histamine receptors (11). These receptors are composed of five structurally similar subunits arranged in a ring to form a central ion-conducting pore (12).…”
mentioning
confidence: 99%
“…A number of invertebrate species are known to express LGIC types that cross the ligand specificity/ion selectivity boundaries as present in vertebrates (Cully et al, 1994(Cully et al, , 1996Horoszok et al, 2001;Gisselmann et al, 2002;Beg and Jorgensen, 2003;Putrenko et al, 2004). Our findings show that anionic nAChRs in L. stagnalis represent true nAChRs that have acquired the ability to conduct anions by specific mutations in the ion channel domain.…”
Section: Evolutionary Perspectivementioning
confidence: 69%
“…LGICs, such as the C. elegans serotonin-gated (Ranganathan et al, 2000) Drosophila melanogaster histamine-gated chloride channels (Gisselmann et al, 2002(Gisselmann et al, , 2004 and the invertebrate inhibitory glutamate receptors (Cully et al, 1994(Cully et al, , 1996Horoszok et al, 2001), appear to originate from mutations in the LBD that induced changes in ligand specificity. This shows that mutations in either LBD or ion channel pore domains functionally contributed to LGIC subtype diversity in invertebrates.…”
Section: Evolutionary Perspectivementioning
confidence: 99%